A new approach to multiplication for gifted children - Kravčenkienė, Violeta; Narkevičienė, Bronė (Lietuvos matematikos rinkinys, 2018)
The article presents the case of mathematical education of gifted children in Kaunas city interdisciplinaryprogram in the third grade. The theoretical basis for such education is the application ofdifferentiated teaching using external differentiation – the program is aimed at the gifted children inthe whole city. Additional aspects of differentiated teaching: grouping of learners according to theskill level, selection of non-standard curriculum content, teamwork and individualized assessment.
Keywords: gifted children; teaching and learning differentiation; mathematics